If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8xy + 5yz + -8yz = 0 Combine like terms: 5yz + -8yz = -3yz 8xy + -3yz = 0 Solving 8xy + -3yz = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3yz' to each side of the equation. 8xy + -3yz + 3yz = 0 + 3yz Combine like terms: -3yz + 3yz = 0 8xy + 0 = 0 + 3yz 8xy = 0 + 3yz Remove the zero: 8xy = 3yz Divide each side by '8y'. x = 0.375z Simplifying x = 0.375z
| 5(3x+8)=47 | | (x^2)/256=x | | 7/10=5/x | | (((x^2)/(256)))-(x)=0 | | x^3-5x^2-10=-8 | | ((x^2)/256)-x=0 | | (2x-5)=-2 | | 190+120+430+x=1000 | | logx=22.9 | | ab^4/ab^5 | | 2(5-d)=2+4d | | q+d=19 | | 2x+8=6-5x | | 1/3(5-x)=6 | | -4(b+5)=-b+7 | | 12y-7y=18 | | y=5x-2-3x+5 | | 6/2x15 | | 8(u+4)-4(u+9)=8 | | 90=3(6x-6) | | 9m+7=5m+27 | | 5(f-1)=15 | | 6z=(0.5z-8) | | -96=2-7(2-4n) | | 4(2y+1)-7y=18 | | 84=6(1+3r)+6 | | 164=-8(1-5n)+3n | | log(12x)-log(2x)+log(3x)=log(8x)+log(9)+log(12) | | y=3e-25x+16e-32 | | 101=-8(X-3)-3x | | 34=x+x+(x-2) | | t/5-7=13 |